2022
DOI: 10.3390/ijms23052685
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy and Apoptosis in Neuropathic Pain Formation

Abstract: Neuropathic pain indicates pain caused by damage to the somatosensory system and is difficult to manage and treat. A new treatment strategy urgently needs to be developed. Both autophagy and apoptosis are critical adaptive mechanisms when neurons encounter stress or damage. Recent studies have shown that, after nerve damage, both autophagic and apoptotic activities in the injured nerve, dorsal root ganglia, and spinal dorsal horn change over time. Many studies have shown that upregulated autophagic activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…It should also be noted that apoptosis is also regulated by proinflammatory cytokines, such as Interferon gamma (IFN-g), tumor necrosis factor-α (TNF-α), interleukina-1 beta (IL-1 b), and IL-6 [ 35 ]. The roles of IL-1 and TNF- α in apoptosis in neurodegenerative diseases such as Alzheimer’s disease were previously described [ 35 , 36 ]. More importantly, it is known that these proinflammatory cytokines have crucial roles in the modulation of neuropathic pain [ 35 , 37 ].…”
Section: Definition and Mechanisms Of Pain—a Brief Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that apoptosis is also regulated by proinflammatory cytokines, such as Interferon gamma (IFN-g), tumor necrosis factor-α (TNF-α), interleukina-1 beta (IL-1 b), and IL-6 [ 35 ]. The roles of IL-1 and TNF- α in apoptosis in neurodegenerative diseases such as Alzheimer’s disease were previously described [ 35 , 36 ]. More importantly, it is known that these proinflammatory cytokines have crucial roles in the modulation of neuropathic pain [ 35 , 37 ].…”
Section: Definition and Mechanisms Of Pain—a Brief Reviewmentioning
confidence: 99%
“…The roles of IL-1 and TNF- α in apoptosis in neurodegenerative diseases such as Alzheimer’s disease were previously described [ 35 , 36 ]. More importantly, it is known that these proinflammatory cytokines have crucial roles in the modulation of neuropathic pain [ 35 , 37 ].…”
Section: Definition and Mechanisms Of Pain—a Brief Reviewmentioning
confidence: 99%
“…Apoptosis plays significant roles in cancer, the immune system, and the response to chemotherapy [ 34 , 35 , 36 ]. Additionally, apoptosis participates in nerve injury and the formation of neuropathic pain [ 37 , 38 ]. However, the specific mechanism of the apoptosis in CIPN ought to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this era, proinflammatory cytokines can encourage autophagic/apoptotic function and subsequent NP formation. Autophagy per se quenches the proinflammatory cytokine activities and further modulates pain behavior ( Liao et al, 2022 ).…”
Section: Molecular Aspects Of Peripheral Neuropathymentioning
confidence: 99%
“…Similarly, these features in glial cells can contribute to worsening outcomes in NP ( Jang et al, 2016 ). It has been documented that autophagy modulation in the DRG neurons can relieve peripheral nerve pain and promote neuronal healing to some extent ( Liao et al, 2022 ). In a recent study, it was suggested that the production of nerve growth factor substantially accelerates debris clearance and improves axonal regeneration via the stimulation of autophagy in a rat model of sciatic nerve crush injury and in vitro Schwann cell culture ( Jadli et al, 2020 ).…”
Section: Autophagy and Analgesiamentioning
confidence: 99%